A study on processing bottled banana-flavored herb tea - Thi Cam Van, Do; Quang Tung, Nguyen; Thi Hanh, Do; Thi Phuong Dung, Nguyen (Journal of Forestry Science and Technology, 2024)
Herb tea is tending to be consumed widely and increasingly in the world. In Vietnam, banana is one of the most popular fruits, but their peels are often wasted which can be reproduced in food processing. The purpose of this study was to determine the combination of banana-flavored water mixed with other herb extraction to create a kind of herbal drink meeting demand’s consumers. Therefore, banana peels were extracted directly in boiling water to create steam and condense water with a strong banana flavor. The optimal volume of banana-flavored water was 25 mL added into 100 mL herbal extract water. Among seven studied herbs, licorice with the number of 2 branches was accepted the most by panelists for herb tea’s sweetness and valued 3.8 for the taste sensory score in the 5 -point Hedonic scale. In addition, saffron with 3 branches was the best coloring agent for bright yellowness, determined 4.2 for the color sensory score. On the other hand, jujube (1 gram) was the best appropriate herb for the best flavour, well mixed with other herbs to produce the best acceptance by major panelists (the total sensory score of 14.6). The final herb tea product made by the selective recepi is potential to supply for the market a new healthy herbal drink.